Upper Oligocene to Pleistocene planktonic foraminifera stratigraphy at North Atlantic DSDP Site 407, Reykjanes Ridge: diversity trends and biozonation using modern Neogene taxonomic concepts - T. M. Weitkamp; T. M. Weitkamp; M. J. Razmjooei; M. J. Razmjooei; P. N. Pearson; H. K. Coxall; H. K. Coxall (Journal of Micropalaeontology)
Deep Sea Drilling Project (DSDP) Site 407, located near the Reykjanes Ridge (southwest of Iceland) offers a rare and extensive record of Late Cenozoic planktonic foraminifera evolution spanning the Neogene and Quaternary periods. This ca. 300 m sequence provides a nearly continuous record of planktonic foraminifera with mostly good preservation quality, aiding the study of pelagic diversity changes over the past 25 million years as the modern North Atlantic Ocean system evolved. Initially investigated in 1979 by Poore, this study presents a taxonomic reassessment of upper Oligocene to Pleistocene planktonic foraminifera at Site 407, including species range documentation, assemblage analysis, biostratigraphic zonation, and age modelling based on planktonic foraminifera, calcareous nannofossils, and scanning electron microscopy. This study employs modern taxonomic perspectives that integrate morphological and stratophenetic frameworks for fossil species with genetic data for taxa having living representatives. Systematic species counts enable quantitative diversity analysis, with a particular focus on the genus Neogloboquadrina, which becomes increasingly prevalent at Site 407 from the late Neogene to Quaternary. The planktonic foraminifera assemblages at Site 407 exhibit a contraction in diversity and a shift in species dominance, notably around 160 m b.s.f. (metres below seafloor) (ca. 8.9–16.5 Ma) and 56 m b.s.f. (ca. 2–3.4 Ma). The upper Oligocene and lower Miocene include species belonging to the genera Catapsydrax, Globoturborotalita, Dentoglobigerina, and Paragloborotalia. An acme of “Ciperoella” pseudociperoensis (lower and middle Miocene), still of uncertain generic affiliation, may have biostratigraphic use. Well-preserved Turborotalita quinqueloba are relatively common throughout the sequence. In Oligocene and Miocene material, T. quinqueloba is accompanied by Tenuitella spp. From the upper Miocene onwards, neogloboquadrinids including Neogloboquadrina praeatlantica, N. atlantica, N. incompta, and N. pachyderma become increasingly common and dominate Pliocene assemblages, together with Globigerina bulloides. Assemblages with an increasingly high-latitude nature, i.e. where N. pachyderma dominates, take over in the lower Pleistocene. Multiple hiatuses are recorded, of which the largest is ca. 8 million years long, separating the middle and upper Miocene (8.9–16.5 Ma; 158.56–160.06 m b.s.f.). Continuous biozonation at Site 407 is challenged by limited species diversity and the absence of standard low-latitude biozone markers, rendering standard schemes ineffective. Recognizable biozones include the low-latitude O7 and M1 Zones in the late Oligocene and early Miocene, respectively; the high-latitude Neogloboquadrina atlantica sinistral Zone in the late Miocene and Pliocene; the Globoconella inflata Zone in the late Pliocene; and the Neogloboquadrina pachyderma Zone in the Pleistocene. The nannofossil biozonation faces similar challenges. A revised biostratigraphic age model integrates calibrated planktonic foraminifera and nannofossil events, incorporating abundant species like “C.” pseudociperoensis, N. atlantica dextral and sinistral, Globoconella puncticulata, G. inflata, and N. pachyderma. These findings are expected to contribute to the Neogene–Quaternary Middle Atlas of planktonic foraminifera and potentially improve the use of neogloboquadrinids in palaeoceanography and biostratigraphy.